UTILIZING ENGINEERS WORKFORCE DIVERSITY TO ENHANCE MANUFACTURING PRODUCTIVITY (Journal of Technology and Operations Management, 2025)
Workforce’s variety and adaptability are critical elements for the manufacturing companies to increase an ability to expand and growth. Lack of workforce diversity has detrimental effects to the employee’s performance and motivation to work better in organisation. Therefore, this study is pertinent to explore the utilization of engineers’ workforce diversity practices in manufacturing companies to enhance the productivity. Specifically, the study involves three main workforce diversity such as recruitment strategy, culture diversity, and generational diversity in order to enhance organisational productivity mainly for the manufacturing companies. The study employed quantitative method involving 200 engineers from the manufacturing company. The findings revealed that all constructs tested were correlated and significance towards manufacturing productivity. The study contributes to the body of knowledge on the workforce diversity practices in helping manufacturing companies to enhance the productivity. It also could be a foundation for future research. Practically, the study helps the manufacturing companies, engineers and managers to strengthens the human resource policies i.e. workforce diversity via developing and planning an effective program in the organisation to improve productivity. Finally, the study also addressed a study limitation, recommendations and conclusion.